PROJECT-BASED LEARNING IN THE PROGRESS OF DEEP LEARNING IN A VOCATIONAL HIGH SCHOOL - Yeni Rahmawati; Rafly Artamy Putra; Abdul Halim (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research investigates the perceptions of students and English teachers at SMK Negeri 15 Samarinda regarding the implementation of Project-Based Learning (PBL) and its role in fostering deep learning in vocational education. Using a quantitative descriptive method, data were collected through structured questionnaires distributed to 90 eleventh-grade Automotive Engineering students and five English teachers. The student questionnaire assessed Experience, Involvement, and Understanding, while the teacher questionnaire examined the Perceived Benefits and Challenges of PBL. The instruments were found to be valid and reliable, with Cronbach’s Alpha values ranging from 0.76 to 0.77. Findings revealed that students generally perceived PBL positively, with mean scores indicating frequent engagement in practical tasks, moderate to high participation, and improved comprehension. Teachers also expressed strong support for PBL, particularly for its ability to enhance critical thinking, collaboration, and independent learning. Although some challenges such as time constraints and resource limitations were noted, they were not viewed as critical barriers. Correlation analysis showed significant relationships among all three student variables at the 0.01 level. Notably, Involvement and Understanding were strong predictors of Experience, as shown by a regression model with a correlation coefficient (R) of .762. Overall, the findings affirm PBL’s effectiveness in promoting deep learning and 21st-century competencies in vocational contexts. While challenges exist, both student and teacher perspectives support PBL as an adaptable and impactful instructional approach. These insights contribute to the growing body of research supporting PBL's application in Indonesian vocational high schools.